EVALUASI PEMBELAJARAN PENDIDIKAN JASMANI OLAHRAGA DAN KESEHATAN DI MTs (MADRASAH TSANAWIYAH) SE-KECAMATAN SEI BALAI - Joko Priono; Imanuddin Siregar; Barham Siregar (Smart Education, 2022)
Abstract: The purpose of this study was to directly analyze the evaluation of learning physical education, sports and health in Private Madrasah Tsanawiyah (MTsS) in Sei Balai District, Batu Bara Regency. This study uses evaluation research methods. The data were analyzed using the Countenance Stake Model. The subjects in this study were PJOK teachers, school principals and MTsS students throughout the Sei Balai District, Batu Bara Regency. The results of the study: (1) Antecedents, Physical Education learning has a good learning plan, because learning planning is made referring to the curriculum adapted to the abilities and needs of students, as well as school conditions, by conducting an initial assessment first. (2) Transaction is the implementation of learning activities that fall into the sufficient category. (3) Outcomes are learning assessments carried out by teachers on physical education learning outcomes that are included in the sufficient category, because they do not fully describe the implementation of learning plans and the implementation of existing learning activities. Keywords: evaluation of learning, model countenance stake Abstrak: Tujuan penelitian ini untuk menganalisis secara langsung mengenai evaluasi pembelajaran pendidikan jasmani olahraga dan kesehatan di Madrasah Tsanawiyah Swasta (MTsS) Se-Kecamatan Sei Balai Kabupaten Batu Bara. Penelitian ini menggunakan metode penelitian evaluasi. Data dianalisis menggunakan Countenance Stake Model. Subjek dalam penelitian ini adalah guru PJOK, kepala sekolah dan siswa MTsS se-Kecamatan Sei Balai Kabupaten Batu Bara. Hasil penelitian: (1) Antecedents, pembelajaran Penjasorkes memiliki perencanaan pembelajaran yang baik, karena perencanaan pembelajaran dibuat mengacu pada kurikulum disesuaikan dengan kemampuan dan kebutuhan siswa, serta kondisi sekolah, dengan melakukan penilaian awal terlebih dahulu. (2) Transaction merupakan pelaksanaan kegiatan pembelajaran yang masuk kategori cukup. (3) Outcomes adalah penilaian pembelajaran yang dilakukan oleh guru terhadap hasil pembelajaran penjasorkes masuk dalam kategori cukup, karena belum sepenuhnya menggambarkan rencana pelaksanaan pembelajaran dan pelaksanaan kegiatan pembelajaran yang ada. Kata kunci: evalusi pembelajaran, model countenance stake